173k views
12 votes
Prove that.
I think the answer won't come 1.​

Prove that. I think the answer won't come 1.​-example-1
User Onivi
by
6.5k points

1 Answer

8 votes

Answer:


{ \rm{ \frac{ {4}^(a + 2) + {4}^(a) }{17 * {4}^(a) } }} \\ \\ = { \rm{ \frac{( {4}^(a) * {4}^(2) ) + {4}^(a) }{17 * {4}^(a) } }} \\ \\ = { \rm{ \frac{ {4}^(a) }{ {4}^(a) } ( \frac{ {4}^(2) + 1}{17}) }} \\ \\ = { \rm{ \frac{ {4}^(2) + 1 }{17} }} \\ \\ = { \rm{ (16 + 1)/(17) }} \\ \\ { \rm{ = (17)/(17) }} \\ \\ = 1

hence proved

User Funda
by
5.4k points